Unexpected irreducible femoral hernia during elective operation: what is the best surgical approach? - Hock, Chin Chong; Mohamed Akbar Mohamed Bahari; Shi, Yun Lee; Mohd Firdaus Mohd Hayati (Gazi Universitesi, 2022)
Femoral hernia is rare and commonly presents with incarceration in emergency situations. From the literature review, there is no femoral hernia reported in chronic irreducible presentation. A 44-year-old female, who was planned for an elective hernia surgery for a chronic irreducible inguinal hernia, was discovered to have an irreducible femoral hernia intraoperatively. Herein, we revisit this diagnostic entity, discuss its misdiagnosis and suggest the best surgical approach when such an unexpected situation happens during an operation.